Sur la nature et l’artefact (neuf fragments tisses). Hommage a Francisco Infante - Constantini, Michel (Przegląd Wschodnioeuropejski, 2018)
This article follows our several previous studies in Russian art of the XXth century. It is dedicated to Francisco Infante-Arana (born 1943), Russian painter of Spanish origin, creator of a “new artistic language” (State Prize of the Russian Federation, 1996), author of an original theory of art developed since 1976 and named the “concept of artifact”. If the spiritual continuity between the work of Francisco Infante and that of Kazimir Malevich has already been established for a long time as a commonplace in contemporary art studies (just remember the title of a series of works by Francisco Infante, “Suprematic Games. Hommage to Malevich”, 1968, from the cycle “Spontaneous Games in Nature”), the relationship between the inventor of the concept of artifact and the founder of the abstractionism in painting, Wassily Kandinsky (1866–1944), has not yet been a subject of targeted research. In our current study, we propose to address this uneasy issue by returning to the origins of the philosophical thought, and namely to the speculations on the phenomena of art in their relation to the phenomena of nature. This approach seems justified insofar as the abstractionism radically challenges the very foundations of art, reposing, since ancient times, on the primacy of mimesis, and rebuild this ruined aesthetic system, paradoxically, on the principles which, having been scrutinized more closely, seem not to lack some affinity with the worldview of the first “philosophers”, so-called Presocratics. Thus, our purpose will be to raise the first elements of the Ancient Greek thought that appear at the base of the artistic creation and theoretical representations of Francisco Infante.